2016
DOI: 10.1093/mnras/stw409
|View full text |Cite
|
Sign up to set email alerts
|

ALMA observations of cold molecular gas filaments trailing rising radio bubbles in PKS 0745−191

Abstract: We present ALMA observations of the CO(1-0) and CO(3-2) line emission tracing filaments of cold molecular gas in the central galaxy of the cluster PKS 0745-191. The total molecular gas mass of 4.6±0.3×10 9 M , assuming a Galactic X CO factor, is divided roughly equally between three filaments each extending radially 3 − 5 kpc from the galaxy centre. The emission peak is located in the SE filament ∼ 1 arcsec (2 kpc) from the nucleus. The velocities of the molecular clouds in the filaments are low, lying within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
107
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 114 publications
(199 reference statements)
15
107
1
Order By: Relevance
“…In the Perseus cluster, the velocity structure of the Hα-emitting filaments, which are coincident with detections of CO emission from the IRAM 30 m telescope, traces streamlines underneath a buoyantly rising radio bubble (Salomé et al 2006(Salomé et al , 2011. ALMA observations of molecular gas at the centers of clusters (David et al 2014;McNamara et al 2014;Russell et al 2014Russell et al , 2016Tremblay et al 2016;Vantyghem et al 2016) have shown cold gas filaments extending along the trajectories of radio bubbles. The molecular clouds have either been lifted directly by the bubbles or cooled in situ from warmer, thermally unstable gas lifted in their wakes.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the Perseus cluster, the velocity structure of the Hα-emitting filaments, which are coincident with detections of CO emission from the IRAM 30 m telescope, traces streamlines underneath a buoyantly rising radio bubble (Salomé et al 2006(Salomé et al , 2011. ALMA observations of molecular gas at the centers of clusters (David et al 2014;McNamara et al 2014;Russell et al 2014Russell et al , 2016Tremblay et al 2016;Vantyghem et al 2016) have shown cold gas filaments extending along the trajectories of radio bubbles. The molecular clouds have either been lifted directly by the bubbles or cooled in situ from warmer, thermally unstable gas lifted in their wakes.…”
Section: Introductionsupporting
confidence: 62%
“…These observations now clearly demonstrate that the structure of the largest molecular gas reservoirs located in the most massive galaxies is shaped by the expansion and trajectory of the radio bubbles. Previous sub-mm observations of brightest cluster galaxies have indicated tentative correlations between X-ray cavity axes and the orientations of molecular gas filaments, including ALMA observations of Abell 1835 and PKS 0745-191 (McNamara et al 2014;Russell et al 2016). IRAM observations of the nearby Perseus cluster detected molecular gas coincident with regions of the complex optical emission line nebula, including several filaments of ionized gas that extend toward radio bubbles (Salomé et al 2006(Salomé et al , 2011Lim et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…It is interesting to compare our results with a study of the molecular gas in PKS 0745-191 by Russell et al (2016). Even though NGC 5044 is a group and PKS 0745-191 is a massive cluster, the central dominant galaxies in these two systems have very similar gravitating masses of ∼ 2×10 14 M within 30 kpc (David et al 2009;Sanders et al 2014).…”
Section: Multiphase Gas In the X-ray And Hα Filamentsmentioning
confidence: 78%
“…The single phase ICM Molecular cold gas has been detected in a growing number of cool-core clusters (David et al 2014;Russell et al, 2014Russell et al, , 2016McNamara et al 2014;Edge & Frayer 2003). This is generally believed to be the product of thermally unstable cooling from the hot ICM (McCourt et al 2012;, although other sources, such as merger debris from gas-rich galaxies cannot be ruled out.…”
Section: Uplift Of Cluster Gas By Radio Lobesmentioning
confidence: 99%